Crab pot selectivity improvement and attitude of fishers on the use of modified gear in the blue swimming crab Portunus pelagicus (Linnaeus, 1758) fishery - Picoy-Gonzales, Rizalyn M (2024.)
The blue swimming crab Portunus pelagicus (Linnaeus, 1758) is an integral component of the coastal fisheries in many areas around the world. Similar to other economically-important fisheries, the fishery of P. pelagicus faces some biological and ecological issues including the capture of juvenile or undersized conspecifics, non-target species, and discards, which largely threaten the sustainability of the fishery. Gear modification is one of the proven effective technical measures to improve fishing selectivity by altering the gear's catch composition. In crab pot fisheries, the installation of escape gap is by far seen as the simplest and most cost-efficient modification. However, escape gap designing for crab pots in the Philippines has not been explored yet. Thus, this study aimed to: a) determine the effectivity of escape gap as selectivity tool in crab pots for P. pelagicus, b) evaluate the capture performance of crab pots installed with escape gaps through actual fishing operations, and assess the financial component of the modification and, c) assess the attitude of crab pot fishers toward the use of escape gap in crab pot gears for the P. pelagicus fishery. To achieve the objectives, three separate interrelated studies were conducted. The first study determined the most appropriate escape gap design through a series of laboratory experiments on the gap's shape, size and location in the two types of crab pots, namely: 1) dome type (DCP) and, 2) box type (BCP). The second study was a comparative field fishing trial between the gapped (experimental) and conventional crab pots, and the third experiment related to the socio-economic component of the fishery was an attitude survey involving the crab pot fishers. Results showed that an appropriately designed escape gap is an effective selectivity tool that can be used in the crab pot gears that target P. pelagicus. The field fishing trials showed that the use of escape gap reduced the catch of undersized P. pelagicus and other non-target species without affecting the capture of legal-sized target species, as well as the income of the fishers. A pair of rectangle escape gaps with flap having a size of 48 x 25 mm (L x H) located at L2 for DCP and L5 for BCP is recommended to maximize the deliberate escapement of undersized P. pelagicus while retaining the legal-sized ones. The tool's design is simple, its construction and installation is easy, and the cost of production is minimal which makes it a practical management measure that can be used in the P. pelagicus fishery. The attitude survey generally showed a positive response toward the introduction of escape gap in the fishery. The results suggest that the use of escape gap is a promising measure that can help promote the sustainability of the P. pelagicus fishery in Eastern Visayas.
Dissertation (Doctor of Philiosopy in Fisheries) -- Miagao, Iloilo : University of the Philippines Visayas, July 2024.
Keywords: Blue swimming crab (Portunus pelagisus)